Virtual simulation on breastfeeding and nipple-areolar lesions: prototype development and validation. - Medeiros, Lays Pinheiro de; Sena, Julliana Fernandes de; Rodrigues, Maria Izabel Rezende; Nascimento, Rafael Moreira do; Fonseca, Luciana Mara Monti; Costa, Isabelle Katherinne Fernandes (Acta Paulista de Enfermagem, 2023)
Objective: To develop and validate the content and appearance of the prototype of the Serious game "AleitaGame" on breastfeeding and nipple-areolar lesions. Methods: This is a study carried out in three stages, namely: content selection through a Scoping Review, development of educational software based on the Benitti, Seara and Schlindwen approach, and a methodological study for content validation, technical and pedagogical aspects, carried out with six expert judges on the subject. Descriptive analysis was used in this study, as well as the Content Validity Index for the content assessment instrument. Results: The content of the clinical cases and the simulated scenarios was built from a total of 115 studies and was validated by six judges in relation to the content and the technical-pedagogical aspects, the only ones who presented suggestions in the design and feedback of the game. The final version of the serious game contains different media and gamification resources for an interaction with the theme that deals with the breastfeeding technique as a cause of nipple-areolar lesion in lactating women. Conclusion: The "AleitaGame" prototype was validated by expert judges and is suitable for the final stage of educational software development.